The Use of The Antihistamine Fexafenadine in the Treatment of Children with Seasonal Allergic Rhinitis - Razhabova Iroda Muzaffarovna; Mamutova Peruza Sharafatdinovna; Mamutov Sharafatdin Iskandarovich (Genius Journals, 2023)
The issues of application and efficacy of III generation antihistamine drug fexofenadine (Telfast) at treatment of seasonal allergic rhinitis in children living in Priaralie region (the Republic of Karakalpakstan) are considered in the article. The main drug of the III generation of antihistamine series fexofenadine is characterized. Fexofenadine is high effective drug which pharmacological effect is realized by blockade of H1-histamine receptors of different tissues and stabilization of membrane of mast cells.
Keywords: IgE-antibodies; mast cells; eosinophils; interleukins